Prevention of Early Onset Preeclampsia with Aspirin 150mg - Savita Namdev Kamble; Yuga Mohan Jamdade; Karthik K.M (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Objectives: To study efficacy of aspirin 150 mg for prevention of early onset preeclampsia and to study maternal and fetal outcome. Methods: Hospital based interventional, case-control and prospective study. Study was carried out in tertiary health care center. Pregnant women between 12 to 20 weeks gestation with high risk for preeclampsia were included in the study. Results: Low dose aspirin reduces the incidence of early onset preeclampsia and its severity. Total 34% reduction was seen in the study. The treatment did not hamper the onset of spontaneous labour. Aspirin therapy reduced the incidence of caesarean section by better utero placental blood-flow and reduced IUGR. Conclusion: Aspirin acts as a prophylactic by preventing preterm preeclampsia and severe forms of preeclampsia. The maternal outcome is improved because the risk of severe preeclampsia, APH, PPH and caesarean section is reduced. The fetal outcome is improved in terms of birth weight, reduction in preterm deliveries & IUGR.